Increasing Business Revenue of Student Entrepreneurs of Faculty of Engineering of UNNES through IT-Based Marketing Media Creation Training - Rina Rachmawati; Wulansari Prasetyaningtyas; Godham Eko Saputro; Ifa Nurhayati (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
Several problems that arise from the Entrepreneurship Education program at UNNES: 1) inadequate knowledge and understanding of student entrepreneurs of FT Unnes in the area of Digital Marketing, 2) only 50% of student entrepreneurs of FT Unnes were knowledgeable in product marketing technology . Based on the above-mentioned descriptions, the community services being conducted were: 1) Introduction of several media related to social media and marketplaces. 2) Demonstrating simulations in the use of digital business marketing applications. The program was attended by student entrepreneurs of FT Unnes who had a business for at least 1 year; a total of 48 persons. This program was held on July 18, 2023, at Building E7 FT UNNES. The resource person in this occasion was the owner of CV Bapak Pucung. The program outcome indicated an increase in students’ knowledge from the average pre-test score of 68 to 82 in the post-test. The assessment illustrated that 40% of students’ works were in the very good category, 40% were in good category, and 20% were in quite good category.